Digitalization at Industrial Enterprises as a Component of Their Innovative Development: The Advantages and Disadvantages in the Context of Management - Vishtak Inna V. (Bìznes Inform, 2023)
The article outlines some aspects of the digitalization process at industrial enterprises in the current conditions. It is emphasized that digitalization is a process that should lead to the improvement of communication links and increase the efficiency of industrial enterprises, but this process needs to be managed. It is noted that the relevance of the study of digitalization in the aspect of innovations necessitates constant diagnostics of the key processes of its penetration into the activities of industrial enterprises. The aim of the article is to study the content of the concept of «digitalization» as a component of innovative development of enterprises, to determine the positive and negative aspects of the digitalization process, and the main tasks are to systematize the opinions of scholars on the essence of the concept of «digitalization» and to outline its advantages and disadvantages. The scientific novelty of the results of the study is a closer definition of the essence of the concept of «digitalization» as a component of the innovative development of enterprise in the context of management for the effective operation of industrial enterprises. The results of the research made it possible to establish that digitalization is the process of digitization of information, the use of information and communication technologies for the transformation of business processes, the introduction of digital innovations in the development of industrial enterprises to ensure strategically effective actions in future changes (development) of their activities and in the management of these processes. Innovative development of enterprise means the process of directed regular change of its state, which depends on the innovative potential of the enterprise and the source of which is innovation that creates qualitatively new opportunities for further competitive functioning of the enterprise in the market through the implementation of new solutions, ideas, etc., under the influence of synergistic influence of factors of the both internal and external environment.